Pain Management Methods and Techniques in Lumbar Disc Surgery: A Narrative Review Study - Somayeh Mehrpour; Shahram Shafa; Majid Vatankhah; Mehrdad Malekshoar; Mohammad Sadegh Sanie Jahromi; Tayyebeh Zarei; Mansour Deylami; Fateme Maleki; Roohie Farzaneh (Iranian Journal of Neurosurgery)
Background and Aim: This study examines the complex field of pain treatment related to lumbar disc disorders in a narrative review. Methods and Materials/Patients: Our search strategy involved utilizing specific terms, including ‘pain management,’ ‘lumbar disc surgery,’ ‘methods,’ and ‘techniques.’ We formulated a search query using Boolean operators: (‘Pain management’ OR ‘analgesia’) AND (‘lumbar disc surgery’ OR ‘spinal surgery’) AND (‘techniques’ OR ‘procedures’ OR ‘approaches’ OR ‘methods’) AND ‘narrative review.’ A systematic search was conducted across reputable medical databases including PubMed, MEDLINE, and Cochrane Library. Filters were applied to refine search results based on publication type and date, with a focus on material published within the past two decades to ensure the inclusion of current, high-quality literature. Results: This study synthesized information from several sources, demonstrating the changing methods used to address pain in lumbar disc disorders. The article explored the historical background of medical treatments, emphasized both contemporary surgical and non-surgical methods, and investigated the predicted factors that affect the results. The study investigated the range of surgical incidents and examined the clinical factors to be taken into account for treatments. The value of efficient pain treatment in alleviating chronic back pain and maximizing patient results was emphasized. Conclusion: In conclusion, this review underscores the paramount importance of comprehensive management of lumbar disc pain. It stresses that effective pain control not only alleviates immediate suffering but also plays a pivotal role in ensuring positive surgical experiences, enhancing patient outcomes, and promoting long-term well-being.